Arabic for Dummies - Amine Bouchentouf (For dummies, 2014)
Arabic for dummies, 2nd edition, helps readers start speaking modern standard arabic in no time. Whether readers are students, travelers, or work in business or government, they'll find this title to be packed with practical lessons, cultural facts and handy references. Arabic for dummies, 2nd edition, provides guidance on basic grammar, as well as the necessary vocabulary to make introductions and greetings, use proper etiquette, make small talk, make transportation arrangements, order food and beverages, ask directions, deal with money, shop, access recreation and handle an emergency. It features 25 percent new and revised content, including a revamped, user-friendly organization, design improvements to both pedagogy and organization and a fully updated and expanded audio cd that includes real-life conversations. It also include major updates in addition to all the necessary foundational information the dummies reader needs in order to start reading, writing and speaking arabic, including expanded coverage of grammar, verb conjugations and pronunciations and a refreshed mini-dictionary complete with even more essential vocabulary.